Health Policy Implementation Survey on Residential Health Assessment in the West Lombok - Arif Sofyandi; Karjono Karjono; Kardi Kardi; Murtiana Ningsih (Indonesian Journal of Global Health Research, 2024)
A healthy home is a place of refuge or shelter and a place to rest so as to create a perfect life both physically, spiritually and socially. This research uses healthy home survey research using observation and interview techniques. The instrument in this research was to use the healthy house requirements form according to the Indonesian Ministry of Health No.829/Menkes/SK/VII/1999 concerning residential health requirements. The population in this study were all residents in Selamat Village. This research is a qualitative descriptive research, sampling using a purposive sampling technique. The sampling technique that is in accordance with the wishes of the researcher is purposive sampling. Purposive sampling is a technique for determining research samples that is based on the researcher's consideration of samples that are considered appropriate and representative. The informan in this study was 15 people. The research location is Gunung Jae Hamlet, Sheet Village, Sheet District, West Lombok Regency. As a result of the research, the assessment of healthy houses is seen from 3 aspects, namely house components, sanitation and the behavior of the occupants. Of the 15 houses, there is 1 house that is in the healthy category and 14 houses that are in the unhealthy category.